Fine cooking Italian : 200 recipes for authentic Italian food / Taunton Press - Taunton Press
Features two hundred recipes for Italian home cooking for soups, salads, pizza, pasta, main courses, polenta and risotto, desserts, and more, with step-by-step instructions with photos for cooking techniques and ingredient profiles.